Nature and Status of Bureau of Jail and Management and Penology Against Contraband at Makati City Jail (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Contraband is a major issue behind the walls and can be anything from a “homemade” shank by the inmate or drugs or weapons smuggled into the prison in various ways. The problem is not only different types of contraband in the prison; these problems also include how did it enter the prison, what are several ways to prevent it in the prison, and what are different types of contraband found in prisons. The researchers chose this study to determine the nature and status of Bureau of Jail Management and Penology (BJMP) personnel against contrabands, identify the different items of contraband that exist, and know different measures that can be undertaken to minimize the problem encountered by BJMP personnel against contrabands. The researchers utilized a descriptive method as a research design because this study aimed to describe the nature of the situation as it exists at the time of the study and to explore the causes of a particular phenomenon. The researcher utilized purposive sampling, which is a nonprobability sampling method that occurs when the elements selected for the sample are chosen by the judgment of the researcher. Researchers often believe that they can obtain a representative sample by using sound judgment, which will save time and money. The instruments used in gathering data were a survey questionnaire, interview, and observation. The respondents were described according to different demographic profiles. A total of 40% of the respondents are from the age range of 34–41 years old. A total of 90% of the respondents are male, 80% are married, and 80% are college graduates. Different kinds of contrabands, such as deadly weapons, vices, and gadgets, exist in Makati City Jail. BJMP personnel also encounters common problems against the entry of contrabands in MakatiCity Jail. The results of the study can be used to develop enhancement programs, training, and continuing updates through seminars on the campaign against contraband inside the jail for improved and more effective techniques and procedures.
Keywords: nature and status, Bureau of Jail Management and Penology, contraband, city jail